Concurrence of anemia and stunting and associated factors among children aged 6 to 59 months in Peru. - Alessandra Rivera; Víctor Marín; Franco Romaní (PLOS Global Public Health, 2024)
Anemia and stunting are two health problems in the child population; therefore, their concurrence needs to be quantified. We estimated the prevalence of concurrent anemia and stunting (CAS) in children aged 6-59 months and identified the factors associated with this condition. The data came from the Demographic and Health Survey of Peru (DHS), 2022. The study design was cross-sectional and included 19,191 children. Height and hemoglobin measurement followed the specifications of National Health Institute of Peru. To reduce error in measures, the anthropometry personnel was training, the quality of measuring equipment was ensuring, and protocolized techniques and procedures was applying. Hemoglobin concentration was measured in capillary blood using the Hemocue model Hb 201+. Stunting was defined as a height-for-age Z-score less than minus two standard deviations (SD) from the median, following the 2006 WHO child growth standard. Anemia was classified into mild (10.0 to 10.9 g/dL), moderate (7.0 to 9.9 g/dL), severe (< 7.0 g/dL), and no anemia (11.0 to 14.0 g/dL). We performed a bivariate analysis to evaluate factors associated with CAS. To include variables in the multivariate analysis, we applied a statistical criterion (p < 0.10 in the crude analysis) and an epidemiological criterion. We used a binary logistic hierarchical regression model. The prevalence of CAS was 5.6% (95%CI: 5.2 to 5.9). The modifiable factors associated with higher odds of CAS were: "poorest" (aOR: 3.87, 95%CI: 1.99 to 7.5) and "poorer" (aOR: 2.07, 95%CI: 1.08 to 3.98) wealth quintiles, mother with no formal education or primary (aOR: 2.03, 95%CI: 1.46 to 2. 81), father with no formal education or primary (aOR: 1.55, 95%CI: 1.16 to 2.07), no improved water source (aOR: 1.36, 95%CI: 1.10 to 1.68), no roof with improved material (aOR: 1.49, 95%CI: 1.12 to 1.98) and low birth weight (aOR: 7.31, 95%CI: 4.26 to 12.54). In Peru, five out of every 100 children suffer from anemia and stunting simultaneously; there are modifiable factors that, if addressed, could reduce their prevalence.